The Trading Response of Individual Investors to Local Bankruptcies - Christine Laudenbach; Benjamin Loos; Jenny Pirschl; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
We use data from a German online brokerage and a survey to show that retail investors sharply reduce risk-taking in response to nearby firm bankruptcies, which are not predictive of returns. The e ects on trading are spatially highly concentrated, immediate and not persistent. They seem to operate through more pessimistic expected returns and increased risk aversion and do not reflect wealth e ects or changes in background risks. Investors learn about bankruptcies through immediate coverage in local newspapers. Our findings suggest that non-informative local experiences that make downside risks of stock investment more salient contribute to idiosyncratic short-term uctuations in trading.
Keywords: D14; G11; 330; Individual investors; risk-taking; trading; experiences